(3fXQjI GdGef GdGfSGfi ai GdbGfhf GdOhdi GdeYGUQ (B: s (3eY GTGQI NGUI dOhQ GdjGHGf (B/ s - (3cjfSi gGeGSGcis; (3UdGM GdOjf YGeQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3JPcQ gPg GdQSGdI fXQjI GdGef GdGfSGfi ai GdbGfhf GdOhdi GdeYGUQ hjQcR GdHGMK ai QSGdJg Ydi Gf ef GdeWdhH Gf JSYi GdMcheI GdjGHGfjI Gdi GdYed Ydi JWhjQ GdGef GdGfSGfi ef bhGYO GdGNdGb Gdi bhGYO bGfhfjI Yf WQjb JaYjd GdbGfhf GdOhdi GdehLhO hUjGZI bGfhf Ohdi LOjO ef GdGf aUGYOG hjYJbO GdHGMK Gfg ef Gdege hGdVQhQi HPd GdLghO ef NdGd GdbGfhf GdOhdi GdYGe ef GLd JMbjb GdGef GdGfSGfis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B417-432s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GdGef GdGfSGfis; (3GdbGfhf GdOhdi GdeYGUQs; (3OhQ GdjGHGfs; (3MeGjI GdaQOs; (3Mbhb GdGfSGfs; (3GdSjGOIs; (3GdGef GdGfSGfjs; (3GdGee GdeJMOIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs